Pharmaceutical Industry Funding of Health Consumer Groups in Australia: A Cross-sectional Analysis. (April 2019) - Fabbri, Alice; Swandari, Swestika; Lau, Edith; Vitry, Agnes; Mintzes, Barbara
Relationships between consumer organizations and pharmaceutical manufacturers are the focus of transparency efforts in some jurisdictions, including Australia. This study describes the frequency and nature of industry sponsorship of Australian health consumer organizations and examines the link between sponsorship of the most highly funded organizations and manufacturers' requests for public reimbursement of products for related health conditions. We downloaded 130 transparency reports covering the period January 2013 to December 2016 from the website of Medicines Australia and carried out a descriptive analysis. For the most heavily funded organizations and their sponsors, we examined Public Summary Documents of the Pharmaceutical Benefits Advisory Committee to identify relevant products under consideration for public reimbursement over the study period. Thirty-four pharmaceutical companies provided 1, 482 sponsorships to 230 organizations, spending a total of AU$34, 507, 810. The top clinical areas in terms of amount of funding received were cancer, eye health, and nervous system disorders. The sponsors of the most highly funded groups were companies that in most cases had drugs under review for public reimbursement for conditions covered by these organizations. Interactions between the pharmaceutical industry and consumer organizations are common and require careful management to prevent biases that may favor sponsors' interests above those of patients and the public.